Error Translation in Public Sign - Sri Minda (Institut Agama Islam Negeri (IAIN) Padangsidimpuan, 2019)
This research aims to analize error translation found in public signs written in English such billboard, shops name, and so on. This research also investigates the reasons of the error. This reserach was designed based on descriptive analysis. The data were taken by taking photosof billboard and shops name in Padangsidimpuan for three weeks. After analyzing the data it was found that there are three types of error translation on public signs they are, spelling error, grammatical error, and wrong choice of word. The data showed that 70% of the total error is spelling error, followed by grammatical error which is 20% and the lowest percentage is wrong choice of word which is 10%. The reason of these errors due to lack of English knowledge. Most of the owner who made the public signs do not know correct spelling or diction in English.